The Correlation Between Social Supportand Self-Regulation toward Academic Procrastination in Students of Universitas Muhammadiyah Purwokerto - Olivianira, Alya; Hikmawati, Isna (Proceedings Series on Health & Medical Sciences, 2022)
Students as subjects of education in higher education cannot be separated from the obligation to do lecture assignments given by lecturers. Students are also required to be able to adjust, regulate and control themselves, including when dealing with busy lecture activities and difficult college assignments. However, many of the students they met tended to use the time they had for just doing entertainment activities instead of having to read lecture material or do assignments. The classic problem that still exists in the world of education, including in universities, is that there are still frequent occurrences of academic procrastination by students. To determine the relationship between social support and self-regulation with academic procrastination in undergraduate nursing students at Muhammadiyah University, Purwokerto. This study used a quantitative descriptive method with a cross sectional approach. The sampling technique used is simple random sampling with a sample of 74 respondents according to the inclusion and exclusion criteria. Statistical analysis using the Pearson correlation test. The results showed that most of the respondents were 20 years old as many as 37 respondents (50%). Gender is mostly female with 48 respondents (64.9%). With a very satisfactory GPA as many as 49 respondents (66.2%). The results of the correlation test on the social support variable obtained a p value of 0.000 and self-regulation of 0.000 which is smaller than = 0.05, meaning Ho is rejected and Ha is accepted so that it can be it can be concluded that there is a relationship between social support and self-regulation with academic procrastination in undergraduate nursing students at Muhammadiyah University of Purwokerto. There is a relationship between social support and self-regulation with academic procrastination in undergraduate nursing students at Muhammadiyah University of Purwokerto.